Sediment transport : - Yang, Chih Ted (McGraw-Hill, 1996)
Theory and practice is organized into the following eight chapters and four appendices:Chapter1- Properties of water and sediment; chapter2- Incipient motion criteria and applications; chapter3- Resistance to flow and bed forms;ch4- Bed-Load transport; ch5- Suspended load transport;ch6- Total load transport;ch7- Comparison and evaluation of sediment transport functions;ch8- Reservoir sedimentation.